How to have the 'ideal' Down syndrome screening discussion at antenatal appointments. (2nd February 2020) - John, Sophie; Kirk, Maggie; Tonkin, Emma; Stuart-Hamilton, Ian
Abstract : This is the fourth in a series of papers. The previous papers inform midwifery practice by providing insight into whether, to what extent and how cognitive status influences understanding of Down syndrome screening information, the importance of tailoring information, and highlighting areas of communication that are effective in facilitating understanding. These findings led to the development of recommendations to inform a 'best practice' model for midwifery communication of screening information within a conceptual framework that recognises the importance of accurate facts, empathic communication and support for decision-making in a woman-centred approach. These recommendations may have wider relevance beyond midwife communication of Down syndrome screening and may impact upon the communication of other screening information provided within antenatal and neonatal screening. It is important that screening information is communicated effectively in light of changes to screening programmes, such as the introduction of non-invasive prenatal testing.